PENGURANGAN PEMAKAIAN SAMPAH PLASTIK SEKALI PAKAI BAGI GENERASI MUDA MELALUI PROGRAM BRING YOUR TUMBLER GOES TO SCHOOL - K. A. Sudiarawan; P. A.H. Martana; T. I.D.W.P. Dewi; P. D.Y. Utami; I. K.W. Dwipayana; I. K.W. Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The problem of managing plastic waste that has a significant impact on environmental quality makes this dedication carried out with the aim that the